The hydrological cycle of water: An interdisciplinary study of philosophy, science, and the Quran - Mohd Ghazali, Ummi Zainab; Sabjan, Muhammad Azizan (‘Abqari Journal, 2025)
This study investigates the evolution of human understanding of the natural water cycle (hydrological cycle) from early philosophical thought to modern scientific models, with a focus on the coherence of Quranic descriptions with contemporary knowledge. Using a qualitative content analysis of historical philosophical texts, scientific literature, and exegetical works on selected Quranic verses, the research applies a comparative approach to trace developments across different perspectives. The findings reveal that early Greek philosophers initiated conceptual speculation about the water cycle, which was further advanced through empirical methods during the Renaissance and Enlightenment. The 19th and 20th centuries, in turn, introduced transformative technological tools that shaped modern hydrological science. Significantly, Quranic verses revealed in the 7th century accurately describe key components of the water cycle, including evaporation, condensation, rainfall, and groundwater flow, in a manner consistent with contemporary scientific understanding. These findings affirm that the Quranic perspective remains scientifically valid across time, illustrating the text’s enduring relevance and its intersection with later scientific discovery.